INFLUENCE DE LA TENEUR EN MATIERES AZOTEES DE LA RATION ALIMENTAIRE SUR LA PRODUCTION LAITIERE DE LA BREBIS ALLAITANTE EN DEFICIT ENERGETIQUE (Sciences & Technologie. C, Biotechnologies, 2007)
The  authors  carried  out  experimental  investigations  on  the  impact  of  a  rather  important  energy deficit of the cover of the need for the ewe associated at various levels with cover with the need nitrogenized on their dairy production measured according to the method oxytocin during the first sixweeks of lactation the results show that the variable quantities of introduced nitrogenized matters do not lead to notable differences in production of milk between the various tested modes and do not modify the growth of the ranges. In addition, the energy deficit did not have an effect on the production of milk since the ewes were able to mobilize the quantity of energy which is missing in their ration starting from their body reserves.